Transformasi Pembelajaran Membaca Pemahaman melalui Model RADEC Berbasis Flipbook Digital - Perdana, Rifandi; Nasution, Ismail Saleh; Sagala, Friska Herawaty (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study aims to transform reading comprehension instruction through the implementation of the RADEC model integrated with digital flipbook media for elementary school students. The research was motivated by the persistently low levels of students’ reading comprehension skills and the urgent need for innovative, technology-driven learning approaches. Employing a classroom action research design, the study was conducted over two cycles and utilized observation, interviews, and documentation as data collection techniques. The findings demonstrate that the integration of the RADEC model with digital flipbooks significantly enhanced students’ reading comprehension abilities, as evidenced by improved learning outcomes in each cycle. This suggests that the RADEC model, when supported by interactive digital media, fosters more engaging and meaningful learning experiences. The study concludes that the RADEC-based digital flipbook model is a practical and effective tool for improving literacy competencies at the primary level and recommends its broader application in elementary education alongside the continued development of digital learning innovations.